Validity of Science Literacy on the Respiratory System in Indonesia’s Merdeka Curriculum - Putri Apriliyani; Endang Susantini; Yuliani Yuliani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study aims to produce a junior high school-level scientific literacy test on the topic of the human respiratory system in the Merdeka Indonesia curriculum. Method: The method used in this study is a modified research and development method. The data collection technique was carried out using the validation method of Aiken calculations. The scientific literacy test instrument was developed using scientific literacy indicators from the adaptation of Gormally et al. (2012) combined with learning objectives. Then it was validated by three validators who are experts in their fields. The validator provides a Likert scale score (1-4) and suggestions as material for consideration for improvement. The validator assesses the instrument based on material substance, construction, and language aspects. The research data were analyzed quantitatively and descriptively. Results: The results of the validation were then carried out by Aiken calculations, with very valid results, namely the value of V ≤ 0.80 on the substance aspect of 0.89, the construction aspect of 0.94, and the language aspect of 0.93. The scientific literacy instruments developed are valid and can be used to measure the scientific literacy of junior high school students in the Merdeka Indonesia Curriculum. Novelty: This research can provide an overview of scientific literacy instruments per the Merdeka curriculum, which can motivate teachers to train in scientific literacy.